Scanning probe microscopy from the perspective of the sensor - Stirling, Julian (2014)
The class of instruments considered in this thesis, scanning probe microscopes (SPM), raster scan a sensory probe over a surface to form both high resolution images and quantitative interaction measurements. Understanding and extracting information from SPM data has been considered extensively in the three decades since the first SPM. Major developments tend to be greeted with their own theory and data analysis techniques. The more gradual evolution of equipment has not, however, attracted the same level of theoretical consideration.